Trafficking in women in Serbia and neighboring countries: Scope, characteristics and causes - Nikolić-Ristanović Vesna Ž. (Temida)
In this paper scope, characteristics and causes of sex trafficking in women are analyzed. The analysis considers trafficking in women in Serbia and in its direct and indirect surrounding. Available data about distribution and channels of trafficking in women, as well as about methods of recruitment, transfer and victimization of women are analyzed. Also, some of characteristics of traffickers are considered. The special chapter deals with factors that contribute to sex trafficking in women. These factors are classified in three groups: push factors, pull factors and facilitating factors. In the conclusion, the author points out the importance of data exposed in this paper for building efficient system of struggle against as well as prevention of trafficking of human beings in general, and, of sex trafficking in women, in particular.